Smart Specialization of Workforce Structure in the European Union Countries – Dynamic Analysis Applying Shift-Share Analysis Method - Sobczak, Elżbieta (Comparative Economic Research. Central and Eastern Europe, 2013)
The objective of the hereby paper is to present dynamic analysis and assessment of workforce structure in the European Union countries based on structural and geographical shift-share analysis. Workforce structure in economic sectors, distinguished based on R&D work intensity in the European Union countries in the period of 2008-2010, was the subject of diversification and transformations assessment. Shift-share analysis enabled the decomposition of occurring changes into regional, structural and global effects as well as the identification of the, so called, allocation effect resulting in the classification of the studied countries with regard to combinations of local specialization and competitive advantages. The performed research also allowed for the identification different kinds of workforce structure characterized by smart specialization (significant share of workforce in high-tech manufacturing sector or high-tech services sector) and the assessment of generated structural and competitive effects.